1999
DOI: 10.1176/ajp.156.6.902
|View full text |Cite
|
Sign up to set email alerts
|

Previous Exposure to Trauma and PTSD Effects of Subsequent Trauma: Results From the Detroit Area Survey of Trauma

Abstract: Previous exposure to trauma signals a greater risk of PTSD from subsequent trauma. Although these results are consistent with a sensitization hypothesis, like the results from previous research on PTSD, they do not address the mechanism of increased responsivity to trauma. Long-term observational studies can further elucidate these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
531
3
13

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 771 publications
(590 citation statements)
references
References 30 publications
43
531
3
13
Order By: Relevance
“…While adversity is often negatively related to well-being (Breslau et al 1999;Turner and Lloyd 1995), recent evidence suggests that adversity may also foster resilience, i.e., individuals who experience moderate adversity may be better able to cope with stressful situations or failure and, therefore, report higher well-being (Seery et al 2010;Seery, et al 2013). By experiencing the negative consequences of ADHD from early childhood, those individuals may develop a higher resistance to failure as well as ways to cope with adversity and achieve success against significant odds (Wilmshurst et al 2011).…”
Section: Adhd-like Behavior and The Work Environmentmentioning
confidence: 99%
“…While adversity is often negatively related to well-being (Breslau et al 1999;Turner and Lloyd 1995), recent evidence suggests that adversity may also foster resilience, i.e., individuals who experience moderate adversity may be better able to cope with stressful situations or failure and, therefore, report higher well-being (Seery et al 2010;Seery, et al 2013). By experiencing the negative consequences of ADHD from early childhood, those individuals may develop a higher resistance to failure as well as ways to cope with adversity and achieve success against significant odds (Wilmshurst et al 2011).…”
Section: Adhd-like Behavior and The Work Environmentmentioning
confidence: 99%
“…Number of lifetime traumas may be an important confounder between the relationship between PTSD and chronic medical conditions since 1) individuals with PTSD are more likely to have experienced multiple traumatic events in their lifetime (Breslau, Chilcoat, Kessler, & Davis, 1999;Brewin, Andrews, & Valentine, 2000;Scott, 2007) and 2) multiple lifetime traumatic events have been related to chronic medical conditions (Cloitre et al, 2001;Dong et al, 2003;Dong et al, 2004;Felitti et al, 1998). The present study sought to extend prior research by using data from the National Comorbidity Survey Replication (NCS-R) (Kessler & Merikangas, 2004) to examine the relationship between number of lifetime traumas, PTSD and fifteen self-reported chronic medical conditions.…”
mentioning
confidence: 99%
“…Initial symptom severity and prior mental illness can be strong risk factors for later PTSD (Brewin et al, 2000; Ozer et al, 2003). Furthermore, epidemiological studies also reported higher prevalence of PTSD in women, in people living in areas with high community violence, and in victims of interpersonal trauma (Breslau, Chilcoat, Kessler, & Davis, 1999; Breslau et al, 1998; Goldmann et al, 2011; McLean, Asnaani, Litz, & Hofmann, 2011). These population factors, as well as sample sizes and assessment time, may all have contributed to differential PTSD prevalences between studies (Matsuoka, Nishi, Yonemoto, Nakajima, & Kim, 2009b; O’Donnell, Creamer, Bryant, Schnyder, & Shalev, 2003).…”
Section: Discussionmentioning
confidence: 99%